2017
DOI: 10.1111/ggi.13143
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity predicts falls among community‐dwelling older adults in Singapore

Abstract: Aim: The present study examined whether ethnicity independently predicted future falls among community-dwelling older Singaporeans, and whether ethnicity moderated the relationships between falls risk factors at baseline and falls at follow up.Methods: Data from a longitudinal survey of older Singaporeans were used. Baseline assessment included handgrip strength, global cognitive function, mobility difficulties, health and psychosocial status. One-year retrospective falls information at follow up was the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The incidence of falls observed in our study was comparable to two recent studies conducted in Singapore (incident of falls: 14%, 18 age standardised rate for falls: 13.8% 30 ). In our pooled analysis, we observed older age, presence of pre-frailty and the presence of depression or feeling depressed/anxious to be associated with incident falls.…”
Section: Discussion/conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of falls observed in our study was comparable to two recent studies conducted in Singapore (incident of falls: 14%, 18 age standardised rate for falls: 13.8% 30 ). In our pooled analysis, we observed older age, presence of pre-frailty and the presence of depression or feeling depressed/anxious to be associated with incident falls.…”
Section: Discussion/conclusionsupporting
confidence: 89%
“…Risk factors included participants’ sociodemographic characteristics (age, sex, ethnic group), polypharmacy, sensory function, alcohol intake, depression status, self-reported pain, loneliness status and frailty status at baseline. These risk factors were included as they have been reported in literature to increase an individual’s risk of falling 7 18–21…”
Section: Methodsmentioning
confidence: 99%
“…One novel finding was that being non-Chinese was associated with lower participation of ILI surveillance. This could be because of ethnic disparities in socioeconomic status and in turn health care-seeking behaviors in Singapore that favor the major Chinese group over the minority groups [30,31].…”
Section: Xsl • Fomentioning
confidence: 99%
“…Although there are many studies of falls risk factors and falls prevention interventions, the majority of these have been undertaken in Western countries (1,12). There have been a small number of studies that have reported falls incidence in Asian nations such as Taiwan (8,13), Japan (14,15), Korea (16)(17)(18), Hong Kong (13), Singapore (19,20), and Thailand (21). These small number of studies have reported varying rates of falls, between 10 and 33%, for the proportion of older people falling in Asian countries in a 12 month period (7).…”
Section: Introductionmentioning
confidence: 99%